2006
DOI: 10.1373/clinchem.2005.065425
|View full text |Cite
|
Sign up to set email alerts
|

Human P2X7 Pore Function Predicts Allele Linkage Disequilibrium

Abstract: Background: Innate immune response amplification is achieved by leukocyte expression of the purinergic nucleotide receptor P2X 7 , an extracellular nucleotidegated pore. Previously, low P2X 7 pore activity in whole blood was associated with loss-of-function genotypes in correlation with a decreased ratio of lipopolysaccharidestimulated tumor necrosis factor-␣ to interleukin-10, of relevance to a variety of infectious and inflammatory disorders. We hypothesized that evaluation of participants with discordance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 47 publications
4
64
0
Order By: Relevance
“…Moreover, significant synergism was observed in the chimeric variant (AE). These results indicated that A348T is a weak gain-of-function SNP, consistent with those reported by Denlinger et al [58].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, significant synergism was observed in the chimeric variant (AE). These results indicated that A348T is a weak gain-of-function SNP, consistent with those reported by Denlinger et al [58].…”
Section: Discussionsupporting
confidence: 93%
“…Construct DR with C-terminus of the cysteine-rich domain 1 (CRD 1) of P2X 7 critical for regulation of pore formation Position 166aa is located in the C-terminal portion (around exon 5) of the cysteine-rich domain 1 (CRD1) of human P2X 7 . Both gain-of-function and loss-of-function mutations have been reported previously in this region [58,59] in addition to the A166G reported in this study. The region is located between the last two cysteine residues of CRD1.…”
Section: Characterization Of P2x 7 Mutants With Single Nonsynonymous supporting
confidence: 78%
See 3 more Smart Citations